“Diversity of condricthyes and osteichthyes in three marine ecosystems: mangrove, coral reef and rocky of the sub-tidal zone at san cristóbal island”. - Vaca Pita., Ernesto Leandro (Revista Universidad de Guayaquil, 2012)
The present research was done in San Cristóbal – Galápagos applying the lineal transects methodology in three types of ecosystems which are coral, rocky and mangrove, using a 50 meters line to do the transects and taking the fish data about specie and number of individuals. There were chosen five sub tidal places around the island: Isla Lobos, Las Negritas, La Tortuga, Rosa Blanca and Punta Pitt, since february to august 2010. We identified a total of 66 species between 32 families, just the 10% resulted to be endemic to Galápagos, the most part of the species registered for this research were wide distribution species and panamic. There were detected differences between diversity, dominance and specific richness between mangrove – rocky and mangrove – coral ecosystems, comparing the temporal differences for each site, just in Las Negritas were evidence of these differences (two ways ANOVA, Tukey P< 0,05). The fish community structure, the corals and rocky ecosystems were similar, while the mangroves resulted different referring to the other ecosystems.
Keywords: Transects; diversity; dominance; specific richness